2014
DOI: 10.1021/es405468p
|View full text |Cite
|
Sign up to set email alerts
|

Pre-site Characterization Risk Analysis for Commercial-Scale Carbon Sequestration

Abstract: This study develops a probability framework to evaluate subsurface risks associated with commercial-scale carbon sequestration in the Kevin Dome, Montana. Limited knowledge of the spatial distribution of physical attributes of the storage reservoir and the confining rocks in the area requires using regional data to estimate project risks during the pre-site characterization analysis. A set of integrated Monte Carlo simulations are used to assess four risk proxies: the CO2 injectivity, area of review (AoR), mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 31 publications
0
68
0
Order By: Relevance
“…Although there are few published works that use the RSM methods in the sensitivity analysis and optimization of chemical flooding so far, this mathematical tool has been successfully applied in other geological uncertainty processes. The main effect method which displays first-order Sobol indices for the response surface was used for uncertainty and sensitivity analysis on assessing the CO 2 injectivity, area of review and gas migration rate in the work of Dai et al for carbon sequestration [24]. In the recent research of Dai et al the response surface analysis was conducted by using the multi-variate adaptive regression spline for the risk factor metric in CO 2 injection and storage [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few published works that use the RSM methods in the sensitivity analysis and optimization of chemical flooding so far, this mathematical tool has been successfully applied in other geological uncertainty processes. The main effect method which displays first-order Sobol indices for the response surface was used for uncertainty and sensitivity analysis on assessing the CO 2 injectivity, area of review and gas migration rate in the work of Dai et al for carbon sequestration [24]. In the recent research of Dai et al the response surface analysis was conducted by using the multi-variate adaptive regression spline for the risk factor metric in CO 2 injection and storage [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the fall in oil prices has contributed to the fact that many EOR projects are facing cancellation or delay, but the tertiary techniques including CO 2 -EOR for improving the production of partially depleted reservoirs is still an attractive option. A survey in 2014 showed that miscible CO 2 floods yielded 292,735 bbls per day, which accounted for 38% of oil production for EOR processes in the USA [5][6][7][8][9][10]. The EOR potential evaluation, which assessed more than 200 onshore oilfields of 17 different worldwide oil reserved districts, indicates that China has great EOR potential [11].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrofacies and hydraulic conductivity (K) distributions in alluvial fans are generally non-stationary (Weissmann et al, , 2013Anderson, 2007;Zhu et al, 2016a). Hence, the use of these methods may cause large characterization errors and add significant uncertainty to the predictions achieved by groundwater flow and contaminant transport models (Eggleston and Rojstaczer, 1998;Irving and Singha, 2010;Dai et al, 2014a). Zhu et al (2016a) adopted a local-stationary assumption by dividing the alluvial fan into three zones along the flow direction of the Chaobai River, China.…”
Section: Introductionmentioning
confidence: 99%